A method for preventing corrosion and fouling of the inner wall of a ship's seawater pipe

By using polyurea resin coating on seawater pipes, the problem of coatings easily falling off and blocking the pipeline in the prior art is solved, and stronger adhesion and durability are achieved, ensuring the normal operation of the seawater pipe system and the safe navigation of the ship.

CN119331495BActive Publication Date: 2025-03-14TIANJIN ZHITONG NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411886094.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-14
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In the prior art, the anti-corrosion coating of seawater pipelines is prone to fall off due to external impact or welding operations during construction and use, blocking the pipeline, affecting the normal operation of the seawater pipeline system and bringing ship safety hazards.

Method used

The inner wall of the pipe is treated with a polyurea resin coating and sandblasted by a dry compressed air device. Then, after the polyurea resin coating components A and components B are fully stirred at 85°C, mechanically sprayed on the inner wall of the pipe, and repeated spraying until the coating thickness is 1.5~2.5mm, forming a dense micro-nano structure to enhance adhesion and corrosion resistance.

Benefits of technology

The polyurea resin coating has stronger adhesion and longer durability, which can effectively prevent the coating from falling off and blocking the pipeline, ensuring the normal operation of the seawater pipe system and the safe navigation of the ship.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a method for preventing the inner wall of a ship's seawater pipe from being corroded and fouled, and relates to the field of ship protection technology. The present invention is applied to a composite material anti-corrosion coating and anti-fouling technology for the inner wall of a ship's seawater pipe. The coating has excellent anti-corrosion and anti-fouling capabilities, excellent mechanical impact resistance, and good adhesion between the coating and the pipe wall substrate, which perfectly demonstrates the dual protection technology of the coating's anti-corrosion and anti-fouling. The coating prepared by the present invention is composed of polyurea modified resin, inorganic antibacterial powder and other additives and solvents. Compared with traditional polyethylene anti-corrosion coatings, it has better corrosion resistance and mechanical impact resistance, and stronger adhesion to the substrate. It will not fall off or even block the pipeline, affect the normal operation of the pipeline system, or even constitute a safety hazard that poses a normal and safe navigation of the ship, which may occur when polyethylene materials are used as anti-corrosion coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ship pipeline inner surface protection, in particular to a method for preventing the inner wall of a ship seawater pipe from being corroded and contaminated. Background Art

[0002] During the voyage of a ship, a large number of marine organisms will grow on the bottom of the ship. The fouling of marine organisms will increase the resistance of the ship during navigation, resulting in a decrease in navigation speed and an increase in fuel consumption costs. At the same time, the cleaning of marine organisms from the bottom of the ship during ship closure and docking will bring huge additional maintenance costs. The global shipping industry will suffer huge economic losses to the entire industry every year due to marine organism fouling. The growth of marine organisms also brings the same problems to subsea valves and seawater pipe systems that use seawater as the medium.

[0003] In recent years, the rapid development of marine engineering projects such as ocean shipping and marine energy development has greatly increased the utilization rate of ships and related equipment. How to ensure that ships can sail and operate safely is the most noteworthy issue. The seawater pipes on ships are mainly composed of metal structures. In environments with high corrosion, high humidity, and alternating dry and wet conditions, the pipes will accelerate the loss and affect the normal operation of the seawater pipe system. As an existing mature process method, polyethylene (PE) anti-corrosion coating has become a widely accepted seawater pipe anti-corrosion material in the industry due to its excellent resistance to seawater corrosion. However, the polyethylene-coated pipes are easily damaged by external impact or welding slag splashing during the lifting and on-site pre-installation process, which may cause the coating to fall off and block the pipe during subsequent operation, posing a great safety hazard to the navigation of ships, thus becoming a headache for shipyards and shipowners.

[0004] The invention patent with the authorization announcement number CN110564279B discloses "a marine engineering anticorrosive polyurea coating and its preparation method". The disclosed polyurea coating is composed of polyisocyanate and polycarbonate polyol as component A, and component B is composed of amino-terminated polyether, amino chain extender, modified nano titanium dioxide, nano zinc oxide, hydroxyaminocarboxylic acid compounds, antifouling agent, antirust pigment, anti-settling agent, etc. In addition to the need for mixing and reacting under high temperature and high pressure, there is no evidence that the coating can effectively inhibit the growth of marine organisms in seawater environment; in addition, the base resin is mainly composed of amino-terminated polyether. If it is immersed in seawater for a long time, ether bond cleavage reaction is likely to occur, which may destroy the integrity of the coating and cause the coating's anticorrosion function to fail.

[0005] The invention patent with authorization announcement number CN109401603B announced "a polyurea elastomer anti-corrosion material and its preparation and use method", disclosing a polyurea elastic coating, which consists of terminal amino polyolefin, rubber plasticizer, anti-penetration agent, acid-resistant filler, high-temperature resistant filler, carbon black, etc. as component A, and consists of polyisocyanate, polymer polyol, etc. as component B. It has good anti-corrosion performance against strong alkali and mixed acid, but has not proved its corrosion resistance to seawater and anti-biological adhesion effect, and has no guiding significance for its application in anti-corrosion coating of seawater pipes.

[0006] In summary, in the prior art, except for polyethylene powder coating, polyurea or modified polyurea materials rarely obtain substantial application in the field of marine engineering, especially in the sub-field of seawater pipeline corrosion protection. The reason may be that the process of the coating in construction does not meet the expected requirements, or the anti-corrosion and anti-fouling effects of the coating are not satisfactory. In order to overcome the shortcomings of the prior art, it is necessary to develop a new anti-corrosion coating that can be applied to the inner surface of seawater pipes. In addition to having the same seawater corrosion resistance as polyethylene materials, the anti-corrosion coating should also have better anti-fouling properties than polyethylene coatings, better mechanical impact resistance and stronger adhesion to the pipe wall substrate. In this way, the coating will not fall off or crack due to external force impact, and it also provides guarantees for the normal operation of the pipeline system and the safe navigation of ships. Summary of the invention

[0007] The object of the present invention is to provide a method for preventing the inner wall of a ship's seawater pipe from being corroded and contaminated, so as to solve the problems existing in the prior art. Similarly, the method can also be further applied to other pipes, valves and hulls using seawater as a medium.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preventing the inner wall of a ship seawater pipe from being corroded and fouled, the preparation steps of which are as follows:

[0009] (1) Use dry compressed air to blow the inner wall to complete the cleaning;

[0010] (2) Sandblasting the cleaned inner wall of the pipe;

[0011] (3) After 100 parts by weight of component A of the polyurea resin coating and 0.1 to 1 part of component B of the polyurea resin coating are fully stirred at 85° C. for 1 hour, the mixture is mechanically sprayed onto the inner wall of the pipe pretreated in the above step (2). After spraying, the mixture is dried and cured at room temperature for 24 hours. The above steps are repeated until the coating thickness reaches 1.5 to 2.5 mm, thereby completing the preparation of the polyurea resin coating.

[0012] Furthermore, in step (1), the pipe is made of carbon steel.

[0013] Furthermore, the component A of the polyurea resin coating in step (3) comprises, by weight: 80-150 parts of polyurea modified resin, 100-150 parts of solvent, 5-15 parts of vinyl polydimethylsiloxane, 1-5 parts of 4-pentene-1-sulfonyl chloride, 1-5 parts of pentenesulfonamide, 1-3 parts of tannic acid, and 8-18 parts of inorganic antibacterial powder; and the component B of the polyurea resin coating is di-tert-butyl peroxide.

[0014] Furthermore, the preparation method of the polyurea modified resin is:

[0015] a. Mix 7-9 parts by weight of isothiazolinone and 40 parts by weight of N,N-dimethylformamide, add 18-20 parts by weight of liquid bromine dropwise under stirring at 40-60 rpm, raise the temperature to 61-65°C, keep the temperature for reaction for 3 hours, add 100 parts by weight of deionized water after the reaction is completed, stir evenly and filter, and recrystallize the obtained solid product to obtain brominated isothiazolinone;

[0016] b. Mix 4-6 parts by weight of brominated isothiazolinone and 40 parts by weight of N,N-dimethylformamide, add 1-3 parts by weight of potassium carbonate and 3-6 parts by weight of 1,3,5-triaminobenzene in sequence while stirring at 40-60 rpm, slowly heat to 71-75° C., keep warm for 8-10 hours, add 40 parts by weight of water after the reaction is complete, stir evenly and filter, and recrystallize the obtained solid product to obtain an intermediate;

[0017] c. Mix 40 wt % of diphenylmethane diisocyanate / N,N-dimethylformamide solution and 25 wt % of (E)-2,6-diamino-4-ethylenediamine / N,N-dimethylformamide solution, stir to make the two fully mixed, react at room temperature for 3 hours, add the intermediate, stir evenly, then evaporate the solvent at 50-60° C. and continue to react for 5 hours, finally evaporate the solvent at 90° C. and continue to react until constant weight; the mass ratio of diphenylmethane diisocyanate, (E)-2,6-diamino-4-ethylenediamine, and the intermediate is 0.5-1.6:3.7:0.4-1.1.

[0018] Furthermore, the preparation method of the inorganic antibacterial powder is as follows: placing silver powder with a particle size of 15 to 50 μm in a grinding jar with a grinding speed of 600 to 1500 rpm, adding a mixed solution of ethanol and water to a solid content of 1 to 25 wt%, the mass ratio of ethanol to water is 9:1, grinding for 5 to 25 minutes, adding 5-hexenyltrimethoxysilane and iron oxide with a particle size of 15 to 50 μm, the amount of 5-hexenyltrimethoxysilane is 1 to 10 wt% of the silver powder, grinding for 5 to 40 minutes, adding cuprous oxide with a particle size of 15 to 50 μm, grinding for 5 to 40 minutes, centrifuging to obtain the solid, and drying at 100 to 110° C. for 10 hours.

[0019] Furthermore, the mass ratio of the silver powder, iron oxide and cuprous oxide is 1:2:3.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] Compared with the traditional polyethylene coating, the polyurea resin coating prepared by the present invention has stronger adhesion to the inner wall surface of the pipeline and longer durability. Even if used for a long time, the anti-corrosion coating of the present invention will not crack, and will not fall off or even block the pipeline, affect the normal operation of the pipeline system, or even pose a safety hazard to the normal and safe navigation of the ship, which may occur when the polyethylene material is used as the anti-corrosion coating;

[0022] The inorganic antibacterial powder of the present invention selects cuprous oxide, ferric oxide, and silver, and is ground and modified together with 5-hexenyltrimethoxysilane. During the grinding process, the time and order of adding the three are controlled to obtain inorganic powders of different particle sizes, which can be embedded in the sandblasting roughened surface, so that the coating forms a dense micro-nano structure. On this basis, the double bonds introduced on the surface of the powder by grinding modification can form chemical bonds with the polyurea resin coating, thereby locking the powder in the coating to prevent the powder from falling off. At the same time, the combination of the two introduces the hydrophobic group on the surface of the inorganic antibacterial powder into the molecular structure of the polyurea resin, and together with the micro-nano structure surface, the hydrophobic group is isolated from seawater penetration, thereby improving the corrosion resistance and anti-fouling performance of the coating.

[0023] The polyurea resin coating used in the present invention comprises polyurea modified resin, vinyl polydimethylsiloxane, 4-pentene-1-sulfonyl chloride, pentenesulfonamide, tannic acid, inorganic antibacterial powder and solvent. The polyurea modified resin is obtained by brominating isothiazolinone, combining it with the amino group of 1,3,5-triaminobenzene, and polymerizing the remaining unreacted amino group with diphenylmethane diisocyanate and (E)-2,6-diamino-4-ethylene acid to obtain a resin. Antifouling active groups are introduced into the side chains to improve the antifouling effect of the coating. The rigid benzene ring structure in the main chain makes the coating hard, with excellent wear resistance, good scratch resistance and excellent impact resistance. In addition, during the curing and drying process, the components of the polyurea resin coating and the inorganic antibacterial The bacterial layer is cross-linked and polymerized with carbon-carbon double bonds to form an interpenetrating cross-linked network, which enhances the impact strength of the surface coating. The Si-O-Si soft chain segment in the cross-linked network makes the coating still in a highly elastic state in low-temperature sea areas, with good flexibility, which is conducive to the optimization and improvement of impact resistance. The interpenetrating cross-linked network can further improve the density of the surface layer and enhance the corrosion resistance of the coating. At the same time, the auxiliary coordination of Si-O-Si chain segments and hydrophobic groups forms a low surface energy anti-biological adhesion effect, which effectively guarantees the anti-fouling performance. In addition, 4-pentene-1-sulfonyl chloride and pentenesulfonamide in the polyurea resin coating can react with solvents or a small amount of water infiltrated from the outside, and the generated sulfonic acid groups help to improve the adhesion of the coating.

[0024] The composite coating material and antifouling technology used for the inner wall of the pipeline of the present invention ensure good adhesion between the coating and the pipe wall substrate, perfectly demonstrating the dual protection technology of the coating's anti-corrosion and anti-fouling properties, and having strong resistance to mechanical impact. The protection technology of the present invention can also be further applied to other pipes, valves and hulls that use seawater as a medium, and has broad application prospects. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] In order to more clearly illustrate the method provided by the present invention, the following examples and comparative examples are used to describe in detail. The component A and di-tert-butyl peroxide prepared in the examples and comparative examples are used to prepare coatings in corresponding proportions. A carbon steel sample is taken and subjected to the same treatment steps as in the examples and comparative examples. After the preparation is completed, antifouling, corrosion resistance and impact resistance tests are performed. The test methods are as follows:

[0027] Antifouling performance: refer to the national standard "Antifouling paint sample shallow sea immersion test method" (GB5370-85), and test the marine organism attachment rate once after 6, 12, 18 and 24 months.

[0028] Corrosion resistance: A neutral salt spray test was conducted using an SH-60 salt spray test chamber. The sample was placed in the test chamber at a certain angle. A 5% NaCl solution was prepared and added to the salt water storage device of the salt spray chamber. The temperature was set to 35°C, and then a continuous neutral salt spray test was conducted. The test cycle was 720 hours. During the test, the changes in the surface of each group of coating samples were recorded and observed. After the neutral salt spray test was completed, the corroded macroscopic sample surface was rated according to the standard.

[0029] Impact resistance: tested according to ASTM D2794 method.

[0030] The test methods for various indicators of the coating in the following examples and comparative examples are as follows:

[0031] Adhesion: According to GB / T5210-2006 Determination of Coating Adhesion - Pull-off Method, wipe the surface of the sample to ensure the cleanliness of the sample surface, mix it evenly with a specific adhesive in a ratio of 1:1, apply it on the test column, and place the test column (20mm in diameter) directly on the surface of the test sample coating to avoid movement and reduce the generation of bubbles; after the adhesive is cured, use a special cutter to cut through the coating to expose the substrate, ensuring that the pull-off test area is 100πmm 2 , connect the fully automatic digital pull-off adhesion tester to the test column, set the pull-off speed and limit measurement value of the instrument to a suitable range, perform the pull-off test until the coating is damaged, and record the pull value at this time. Test at least 3 times and take the average value.

[0032] Example 1; (1) Using a dry compressed air device to blow the inside of the pipeline to complete the cleaning;

[0033] (2) The inner wall of the cleaned pipe is sandblasted to roughen the surface to Sa 2.5 level;

[0034] (3) silver powder with a particle size of 15 μm is placed in a grinding jar with a grinding speed of 800 rpm, a mixed solution of ethanol and water is added to a solid content of 10 wt%, the mass ratio of ethanol to water is 9:1, grinding for 10 min, 5-hexenyltrimethoxysilane and iron oxide with a particle size of 20 μm are added, the coupling agent is used in an amount of 8 wt% of the silver powder, grinding for 15 min, cuprous oxide with a particle size of 50 μm is added, grinding for 15 min, the solid is centrifuged, and dried at 100 ° C for 10 h to prepare an inorganic antibacterial powder; the mass ratio of the silver powder, iron oxide, and cuprous oxide is 1:2:3;

[0035] (4) 7 parts by weight of isothiazolinone and 40 parts by weight of N,N-dimethylformamide were mixed, 18 parts by weight of liquid bromine was added dropwise under stirring at 60 rpm, the temperature was raised to 64°C, and the reaction was kept warm for 3 hours. After the reaction was completed, 100 parts by weight of deionized water was added, the mixture was stirred evenly, and then filtered, and the obtained solid product was recrystallized to obtain brominated isothiazolinone;

[0036] (5) 4 parts by weight of brominated isothiazolinone and 40 parts by weight of N,N-dimethylformamide were mixed, and 1 part by weight of potassium carbonate and 3.5 parts by weight of 1,3,5-triaminobenzene were added in sequence under stirring at 60 rpm, and the temperature was slowly raised to 72° C. and kept for 10 hours. After the reaction was completed, 40 parts by weight of water was added, and the mixture was stirred evenly and filtered, and the obtained solid product was recrystallized to obtain an intermediate;

[0037] (6) Mixing 40 wt % of diphenylmethane diisocyanate / N,N-dimethylformamide solution and 25 wt % of (E)-2,6-diamino-4-ethylenediamine / N,N-dimethylformamide solution, stirring to fully mix the two, reacting at room temperature for 3 h, adding the intermediate, stirring evenly, then evaporating the solvent at 60° C. and continuing to react for 5 h, and finally evaporating the solvent at 90° C. and continuing to react until constant weight, to obtain a polyurea modified resin; the mass ratio of the diphenylmethane diisocyanate, (E)-2,6-diamino-4-ethylenediamine, and the intermediate is 0.5:3.7:0.4;

[0038] (7) After 100 parts by weight of component A of the polyurea resin coating and 0.1 parts of di-tert-butyl peroxide are fully stirred at 85° C. for 1 hour, the mixture is mechanically sprayed onto the inner wall of the pipe pretreated in the above step (2). After the spraying is completed, the mixture is dried and cured at room temperature for 24 hours. The above steps are repeated until the coating thickness reaches 1.5 mm, thereby completing the preparation of the polyurea resin coating. Component A of the polyurea resin coating comprises, by weight, 80 parts of a polyurea modified resin, 100 parts of an 85wt% acetone aqueous solution, 5 parts of vinyl polydimethylsiloxane, 1 part of 4-pentene-1-sulfonyl chloride, 1 part of pentenesulfonamide, 1 part of tannic acid, and 8 parts of an inorganic antibacterial powder.

[0039] Example 2; (1) Using a dry compressed air device to blow the inside of the pipeline to complete the cleaning;

[0040] (2) The inner wall of the cleaned pipe is sandblasted to roughen the surface to Sa 2.5 level;

[0041] (3) placing silver powder with a particle size of 30 μm in a grinding jar with a grinding speed of 800 rpm, adding a mixed solution of ethanol and water to a solid content of 10 wt%, the mass ratio of ethanol to water being 9:1, grinding for 15 min, adding 5-hexenyltrimethoxysilane and iron oxide with a particle size of 30 μm, the amount of 5-hexenyltrimethoxysilane being 6 wt% of the silver powder, grinding for 25 min, adding cuprous oxide with a particle size of 40 μm, grinding for 25 min, centrifuging to obtain the solid, and drying at 100 ° C for 10 h to prepare an inorganic antibacterial powder; the mass ratio of the silver powder, iron oxide, and cuprous oxide is 1:2:3;

[0042] (4) 8.16 parts by weight of isothiazolinone and 40 parts by weight of N,N-dimethylformamide were mixed, and 19.7 parts by weight of liquid bromine was added dropwise under stirring at 60 rpm. The temperature was raised to 64° C. and the mixture was kept warm for 3 h. After the reaction was completed, 100 parts by weight of deionized water was added, the mixture was stirred evenly, and then filtered. The obtained solid product was recrystallized to obtain brominated isothiazolinone;

[0043] (5) 5.52 parts by weight of brominated isothiazolinone and 40 parts by weight of N,N-dimethylformamide were mixed, and 1.8 parts by weight of potassium carbonate and 5.5 parts by weight of 1,3,5-triaminobenzene were added in sequence under stirring at 60 rpm, and the temperature was slowly raised to 72° C. and kept for reaction for 10 hours. After the reaction was completed, 40 parts by weight of water was added, and the mixture was stirred evenly and filtered, and the obtained solid product was recrystallized to obtain an intermediate;

[0044] (6) Mixing 40 wt % of diphenylmethane diisocyanate / N,N-dimethylformamide solution and 25 wt % of (E)-2,6-diamino-4-ethylenediamine / N,N-dimethylformamide solution, stirring to fully mix the two, reacting at room temperature for 3 h, adding the intermediate, stirring evenly, then evaporating the solvent at 60° C. and continuing to react for 5 h, and finally evaporating the solvent at 90° C. and continuing to react until constant weight, to obtain a polyurea modified resin; the mass ratio of the diphenylmethane diisocyanate, (E)-2,6-diamino-4-ethylenediamine, and the intermediate is 1.0:3.7:0.7;

[0045] (7) After 100 parts by weight of component A of the polyurea resin coating and 0.5 parts of di-tert-butyl peroxide are fully stirred at 85° C. for 1 hour, the mixture is mechanically sprayed onto the inner wall of the pipe pretreated in the above step (2). After the spraying is completed, the mixture is dried and cured at room temperature for 24 hours. The above steps are repeated until the coating thickness reaches 1.5 mm, thereby completing the preparation of the polyurea resin coating. Component A of the polyurea resin coating comprises, by weight, 100 parts of a polyurea modified resin, 120 parts of an 85wt% acetone aqueous solution, 10 parts of vinyl polydimethylsiloxane, 3 parts of 4-pentene-1-sulfonyl chloride, 3 parts of pentenesulfonamide, 2 parts of tannic acid, and 13 parts of an inorganic antibacterial powder.

[0046] Example 3; (1) Using a dry compressed air device to blow the inside of the pipeline to complete the cleaning;

[0047] (2) The inner wall of the cleaned pipe is sandblasted to roughen the surface to Sa 2.5 level;

[0048] (3) silver powder with a particle size of 30 μm is placed in a grinding jar with a grinding speed of 800 rpm, a mixed solution of ethanol and water is added to a solid content of 10 wt%, the mass ratio of ethanol to water is 9:1, and the mixture is ground for 25 min. 5-hexenyltrimethoxysilane and iron oxide with a particle size of 50 μm are added, the amount of 5-hexenyltrimethoxysilane is 10 wt% of the silver powder, and the mixture is ground for 40 min. Cuprous oxide with a particle size of 50 μm is added and the mixture is ground for 40 min. The solid is centrifuged and dried at 100 °C for 10 h to prepare an inorganic antibacterial powder. The mass ratio of the silver powder, iron oxide and cuprous oxide is 1:2:3.

[0049] (4) 9 parts by weight of isothiazolinone and 40 parts by weight of N,N-dimethylformamide were mixed, and 20 parts by weight of liquid bromine was added dropwise under stirring at 60 rpm. The temperature was raised to 64° C. and the mixture was kept warm for 3 h. After the reaction was completed, 100 parts by weight of deionized water was added. The mixture was stirred evenly and then filtered. The obtained solid product was recrystallized to obtain brominated isothiazolinone;

[0050] (5) 6 parts by weight of brominated isothiazolinone and 40 parts by weight of N,N-dimethylformamide were mixed, and 1.5 parts by weight of potassium carbonate and 6 parts by weight of 1,3,5-triaminobenzene were added in sequence under stirring at 60 rpm. The temperature was slowly raised to 72° C. and the reaction was kept at this temperature for 10 hours. After the reaction was completed, 40 parts by weight of water was added, the mixture was stirred evenly, and then filtered. The obtained solid product was recrystallized to obtain an intermediate;

[0051] (6) Mixing 40 wt % of diphenylmethane diisocyanate / N,N-dimethylformamide solution and 25 wt % of (E)-2,6-diamino-4-ethylenediamine / N,N-dimethylformamide solution, stirring to fully mix the two, reacting at room temperature for 3 h, adding the intermediate, stirring evenly, then evaporating the solvent at 60° C. and continuing to react for 5 h, and finally evaporating the solvent at 90° C. and continuing to react until constant weight, to obtain a polyurea modified resin; the mass ratio of diphenylmethane diisocyanate, (E)-2,6-diamino-4-ethylenediamine, and the intermediate is 1.6:3.7:1.1;

[0052] (7) After 100 parts by weight of component A of the polyurea resin coating and 0.5 parts of di-tert-butyl peroxide are fully stirred at 85° C. for 1 hour, the mixture is mechanically sprayed onto the inner wall of the pipe pretreated in the above step (2). After the spraying is completed, the mixture is dried and cured at room temperature for 24 hours. The above steps are repeated until the coating thickness reaches 1.5 mm, thereby completing the preparation of the polyurea resin coating. Component A of the polyurea resin coating comprises, by weight, 150 parts of a polyurea modified resin, 150 parts of an 85wt% acetone aqueous solution, 10 parts of vinyl polydimethylsiloxane, 5 parts of 4-pentene-1-sulfonyl chloride, 5 parts of pentenesulfonamide, 3 parts of tannic acid, and 18 parts of an inorganic antibacterial powder.

[0053] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that step (3) is different. Step (3) is changed to: silver powder with a particle size of 15 μm, iron oxide, and cuprous oxide are placed in a grinding jar with a grinding speed of 800 rpm, a mixed solution of ethanol and water is added to a solid content of 10 wt %, the mass ratio of ethanol to water is 9:1, and grinding is carried out for 10 min. 5-hexenyltrimethoxysilane and iron oxide with a particle size of 20 μm are added, and the amount of 5-hexenyltrimethoxysilane is 8 wt % of the silver powder. Grinding is carried out for 30 min, and the solid is centrifuged and dried at 100° C. for 10 h to prepare an inorganic antibacterial layer. The mass ratio of the silver powder, iron oxide, and cuprous oxide is 1:2:3. The remaining steps are the same as in Example 1.

[0054] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that 5-hexenyltrimethoxysilane is not added, and the remaining steps are the same as Example 1.

[0055] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that no intermediate is added, and the polyurea modified resin is directly prepared by polymerization of diphenylmethane diisocyanate and (E)-2,6-diamino-4-ethylene acid, and the remaining steps are the same as Example 1.

[0056] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that (E)-2,6-diamino-4-ethylene acid is not added, and the remaining steps are the same as Example 1.

[0057] Comparative Example 5; The difference between Comparative Example 5 and Example 1 is that vinyl polydimethylsiloxane is not added, and the remaining steps are the same as Example 1.

[0058] Comparative Example 6: The difference between Comparative Example 6 and Example 1 is that 4-pentene-1-sulfonyl chloride or pentenesulfonamide is not added, and the remaining steps are the same as Example 1.

[0059] Effect example

[0060] The following Table 1 shows the performance analysis results of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0061] Table 1

[0062]

[0063] From the comparison of the experimental data of the embodiment and the comparative example, it can be found that the protection technology adopted by the present invention has excellent anti-fouling and corrosion resistance, and the formed composite coating has a strong bonding ability with the inner wall of the pipeline and strong impact resistance. In addition, during the test, there is no cracking or falling off of the surface layer. The adhesion of traditional polyethylene coatings is usually 8~10MPa, and the impact strength is usually 0.8~8J. It can be seen that the coating in the present invention is significantly superior to traditional polyethylene coatings in terms of adhesion and impact resistance.

[0064] It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. It should be noted that for those skilled in the art, without departing from the principles of the present invention, it is also possible to use ordinary polyurea materials purchased on the market, or materials with similar properties that have been modified and retouched to ordinary polyurea materials, to achieve the effects of corrosion resistance, antifouling, and mechanical impact resistance of the inner wall of the pipeline. These implementations using ordinary polyurea materials or modified and retouched polyurea materials should also be regarded as the scope of protection of the present invention. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the attached claims rather than the above description, and it is intended to include all changes that fall within the meaning and scope of the equivalent elements of the claims within the present invention. Any mark in the claims should not be regarded as limiting the claims involved.

Claims

1. A method for preventing corrosion and fouling of the inner wall of a ship's seawater pipe, characterized in that: The preparation steps are: Step (1) cleaning the inner wall of the pipeline; Step (2) pre-treating the cleaned inner wall of the pipeline; Step (3) preparing a polyurea resin coating: 100 parts by weight of component A of the polyurea resin coating and 0.1 to 1 part of component B of the polyurea resin coating are stirred at 85°C for 1 hour, and then mechanically sprayed on the inner wall of the pipe pretreated in the above step (2). After spraying, the coating is dried and cured at room temperature for 24 hours, and the above steps are repeated until the coating thickness is 1.5 to 2.5 mm; the component A of the polyurea resin coating comprises, by weight: 80 to 150 parts of polyurea modified resin and 85 parts of acetone. 100-150 parts of t% acetone aqueous solution, 5-15 parts of vinyl polydimethylsiloxane, 1-5 parts of 4-pentene-1-sulfonyl chloride, 1-5 parts of pentenesulfonamide, 1-3 parts of tannic acid, and 8-18 parts of inorganic antibacterial powder; the polyurea modified resin is prepared by brominating isothiazolinone, combining it with 1,3,5-triaminobenzene, and then polymerizing it with diphenylmethane diisocyanate and (E)-2,6-diamino-4-ethylene acid; the B component of the polyurea resin coating is di-tert-butyl peroxide.

2. A method for preventing corrosion and fouling of the inner wall of a ship seawater pipe according to claim 1, characterized in that: The specific process of step (1) is: using dry compressed air to purge the pipeline.

3. A method for preventing corrosion and fouling of the inner wall of a ship seawater pipe according to claim 1, characterized in that: The pipe in step (1) is made of carbon steel.

4. A method for preventing corrosion and fouling of the inner wall of a ship seawater pipe according to claim 1, characterized in that: The pretreatment in step (2) is sandblasting roughening.

5. A method for preventing corrosion and fouling of the inner wall of a ship seawater pipe according to claim 1, characterized in that: The preparation method of the inorganic antibacterial powder in step (3) is as follows: silver powder with a particle size of 15-50 μm is placed in a grinding jar with a grinding speed of 600-1500 rpm, a mixed solution of ethanol and water is added to a solid content of 1-25 wt%, the mass ratio of ethanol to water is 9:1, grinding for 5-25 min, 5-hexenyltrimethoxysilane and iron oxide with a particle size of 15-50 μm are added, the amount of 5-hexenyltrimethoxysilane is 1-10 wt% of the silver powder, grinding for 5-40 min, cuprous oxide with a particle size of 15-50 μm is added, grinding for 5-40 min, centrifuging to obtain the solid, and drying at 100-110° C. for 10 h.

6. A method for preventing corrosion and fouling of the inner wall of a ship seawater pipe according to claim 5, characterized in that: The mass ratio of the silver powder, iron oxide and cuprous oxide is 1:2:3.

Citation Information

Patent Citations

  • A polyurea elastomer anticorrosive material and its preparation and application method

    CN109401603B

  • A marine engineering anti-corrosion polyurea coating and its preparation method

    CN110564279B

  • Polyurea resin composition for water-proof coating with high permeability ann its coating method

    KR102147370B1

  • Structure reinforcement method and structure reinforcement layer using polyurea resin composition

    KR102315914B1